2017
DOI: 10.1016/j.ultsonch.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonication and conventional mechanical homogenization processes on the structures and dielectric properties of BaTiO3 ceramics

Abstract: The effects of the homogenization process on the structures and dielectric properties of pure and Nb-doped BaTiO ceramics have been investigated using an ultrasonic homogenization and conventional mechanical methods. The reagents were homogenized using an ultrasonic processor with high-intensity ultrasonic waves and using a compact mixer-shaker. The components and crystal types of the powders were determined by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analyses. The complex per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is known that the size reduction owing to the ultrasonication can be attributed to mechanical fragmentation and chemical dissolution [24] , [33] , [34] , [35] , [37] . To verify the effect of pH on the dissolution of BaCO 3 , ICP measurements for the supernatant of 600 W ultrasonicated medium were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the size reduction owing to the ultrasonication can be attributed to mechanical fragmentation and chemical dissolution [24] , [33] , [34] , [35] , [37] . To verify the effect of pH on the dissolution of BaCO 3 , ICP measurements for the supernatant of 600 W ultrasonicated medium were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its high calcination temperature (∼1200 °C), solid-state reaction can provide highly dense BaTiO 3 powders, which is desirable in terms of reliability. Furthermore, it has been reported that submicron-sized BaTiO 3 powders can be successfully prepared via the solid-state reaction through appropriate pre-treatments of the raw materials, such as high-energy ball-milling and mechanochemical [29] , [30] , [31] , [32] and sonochemical activation [33] , [34] , [35] . These pre-treatments result in downsizing and uniform mixing of the raw materials, thereby facilitating the synthesis of BaTiO 3 powders through reaction (1).…”
Section: Introductionmentioning
confidence: 99%
“…γ is derived by fitting the modified Curie-Weiss law. For BT-Sb3, γ exhibits a slight decrease inversely proportional to the rise in heat treatment temperature [9][10][11][12]. As for the characteristics of BT-Sb3, EDS/FESEM observations in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, to improve the technological properties and obtain higher-quality products, sumping is used -curing for a certain time and under certain conditions in order to destroy the natural structure, which leads to disintegration of the aggregated particles into elementary grains, an increase in the specific surface and a deepening of the swelling processes, an increase in the number of bound water, an increase in the plasticity and coherence of clay, an improvement in the molding and drying properties [1,2], the leaching of harmful impurities of soluble salts (su chlorites and chlorides) and others. However, in order to save money, many enterprises prefer to work "from the wheels".…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the South Ural State University (Chelyabinsk), the following methods are used to improve the physicomechanical characteristics: mechanical activation, ultrasound and electromagnetic impulses [5], which favorably affects the rheological properties of clay suspensions. Russian [6][7][8][9][10] and foreign scientists [11][12][13][14] dealt with mechanical activation in ceramic systems. A number of works are devoted to questions of possible ways of modifying ceramic masses [1,4,[15][16][17], including using silicon carbide [5][6].…”
Section: Introductionmentioning
confidence: 99%